ESTIMATION OF OIL PRODUCTS CONTENT IN SOIL AND WATER OBJECTS IN THE AREA OF LOCATION OF SLUDGE DRESSERS ON THE COAST OF THE VOLGA RIVER - M.S. Yessenamanova,; A. Shukbarov,; V.F. Zaitsev,; I.V. Melnik,; Zh.S. Yessenamanova,; А.Е. Tlepbergenova, (Academic Scientific Journal of Chemistry, 2020)
The article assesses the quantitative composition of petroleum products at oil waste storage areas near the confluence of the Volga River and its Kizan branch of the Volga Region of the Astrakhan Region. Studies were conducted of soil samples at different depths in two pits and groundwater, groundwater and bottom sediments. In the studied two wells, the maximum excess is observed from 104 to 260 times in the second well, while in the first well the oil content exceeds from 67.5 to 133 times. The content of heavy metals also exceeded the maximum permissible concentration, for example, total chromium 168 times and 2040 times and arsenic 1.7 times and 2.6 times, respectively, in the first and second wells. According to the results of groundwater research, the oil content exceeds 88 and 14.4 times for the 1st oil well and 520 and 86.6 times for the 2nd well. On the Volga River section, located at the 200th distance from the oil, the content of oil products in the water is lower than the MPC, however, far from the coast, the studied indicator is higher than the MPC for fishery reservoirs with a maximum at a distance of 1000 m from the second oil tank. The maximum content of petroleum products (18719.3 ± 4679.8 mg / kg) in bottom sediments was observed in the area of oil tank No. 2, which exceeded the control variant by more than 36 times. Research shows that the second hole is the most polluted